INSTANTANEOUS GLOBAL PLATE MOTION MODEL FROM 12 YEARS OF CONTINUOUS GPS OBSERVATIONS - Prawirodirdjo L.; Bock Y. (My University, 2004)
We estimate a global plate motion model for 17 major and minor tectonic plates solely on the basis of analysis of data from 106 globally distributed continuous GPS stations, spanning the period from January 1991 to July 2003. Site positions estimated from 24-hour segments of data are aligned day-by-day to the International GPS Service (IGS) realization of the ITRF2000 reference frame using a similarity transformation, thereby ensuring that the ITRF2000 no-net-rotation condition is preserved. Linear velocities of a carefully selected set of stations are estimated from the position time series, along with annual and semiannual fluctuations and position offsets due to GPS instrument changes. A white noise plus flicker noise model is applied to estimate realistic uncertainties for the site velocities, which are then propagated into the derived plate motion model parameters. We also examine the vertical velocities in the site selection process. At the Scripps Orbit and Permanent Array Center we have implemented a procedure whereby the plate motion model is updated on a regular (monthly) basis to improve its precision and reliability as new data become available and as a baseline against which anomalous motions can be detected.
Keywords: continuous GPS; global plate motions